SOFTWARE SIMULASI UJIAN NASIONAL BERBASIS MOBILEAPPLICATION MENGGUNAKAN BAHASA PEMROGRAMANJAVA 2 MICRO EDITION (J2ME) - Adhi Wicaksono, Nova Suparmanto, dan Rahmat Hidayat (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
“Software Simulasi Ujian Nasional Berbasis Mobile Application MenggunakanBahasa Pemrograman Java 2 Micro Edition (J2ME)” is a solution and innovation inaddressing the graduation rate of students is getting lower and to increase studentinterest in learning so as to make preparation for the national exam is more mature andis expected to achieve satisfactory results with high rates of graduation. The goal inmaking this software are 1) Can design and create a "National Exam SimulationSoftware", 2) Determine the performance of the "National Exam Simulation Software",and 3) Knowing the advantages "National Exam Simulation Software".Implementation of this research through several steps: 1) Identify needs, 2) Designand Drafting software (Software), 3) Encoding software, 4) Specification of software, 5)Testing software, and 6) Repair and Operation.Based on the stages that have been conducted, the obtained results, a NationalExam Simulation Software. Users can provide the answers A, B, C, D or E on eachquestion are shown. For each correct answer on each question, it will be given points1. Results of questionnaires and interviews on research could also be a reference toimprove the quality of school services in the face of the National Examination. Thisbecomes important because of the percentage of questionnaires and interviews showthat there are indications that needs to be improved services and facilities in the face ofthe UN by the school.Keywords: Software Simulations, National Exam, Mobile Application